The validation of session rating of perceived exertion for quantifying internal training load in adolescent distance runners - Mann, R. H.; Williams, C. A.; Clift, B. C.; Barker, A. R. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To investigate the effect of measurement timing and concurrent validity of session and differential ratings of perceived exertion (sRPE and dRPE, respectively) as measures of internal training load in adolescent distance runners. Methods: A total of 15 adolescent distance runners (15.2 [1.6] y) performed a 2-part incremental treadmill test for the assessment of maximal oxygen uptake, heart rate (HR), and blood lactate responses. Participants were familiarized with RPE and dRPE during the treadmill test using the Foster modified CR-10 Borg scale. Subsequently, each participant completed a regular 2-wk mesocycle of training. Participants wore an HR monitor for each exercise session and recorded their training in a logbook, including sRPE, dRPE leg exertion (dRPE-L), and breathlessness (dRPE-B) following session completion (0 min), 15 min postsession, and 30 min postsession. Results: sRPE, dRPE-L, and dRPE-B scores were all most likely lower when reported 30 min postsession compared with scores 0 min postsession (%change, ±90% confidence limits; sRPE -26.5%, ±5.5%; dRPE-L -20.5%, ±5.6%; dRPE-B -38.9%, ±7.4%). sRPE, dRPE-L, and dRPE-B all maintained their largest correlations (r = .74-.89) when reported at session completion (0 min) in comparison with each of the HR-based criteria measures. Conclusion: sRPE, whether reported 0, 15, or 30 min postsession, provides a valid measure of internal training load in adolescent distance runners. In addition, dRPE-L and dRPE-B can be used in conjunction with sRPE across all time points (0, 15, and 30 min) to discriminate between central and peripheral exertion.